Moderating Effect of Work Self-Efficacy in the Relationship Between Job Resources and Work Engagement of Vocational Business Lecturers - Edokpolor, James Edomwonyi; Jaswal, Vikrant; Owenvbuigie, Robinson; Tee, Tze Kiong (Journal of Technical Education and Training, 2024)
While job resources, work self-efficacy, and work engagement have been investigated extensively, they have not been studied together in the context of vocational business lecturers, despite the low work engagement experienced and the importance of highly resourced and efficacious employees. Therefore, research on the interactive impact of job resources and work self-efficacy on work engagement will fill a gap in the existing literature. The aims of the study were twofold: (1) to investigate the relationships between job resources, work self-efficacy and work engagement, and (2) to investigate the moderating effect of work self-efficacy in the relationship between job resources and work engagement. A quantitative research design was used to achieve the objective of the study. A convenience sampling method was used to select 142 participants, consisting of 12 Heads of Department and 130 lecturers, because they were the available participants as at the time the study was carried out. The correlation statistic was used to answer the research questions. The regression statistic was used to test the direct relationship. The moderation analysis was used to test the indirect relationship. Work engagement positively correlates with job resources and work self-efficacy. Vocational business lecturers who exert high work self-efficacy will likely be engaged on the job. The findings indicate that when job resources and work self-efficacy increase, engagement increases. The study’s findings may provide insights for educational administrators and policymakers on how work engagement will positively impact the job performance of vocational business lecturers and, more broadly, their intention to stay on the job.